Azo Polymers : Synthesis, Functions and Applications - Wang, Xiaogong (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book explores functional polymers containing aromatic azo chromophores in side-chain, main-chain and other parts of their structures, known as azo polymers and which share common photoresponsive properties. It focuses on the molecular architecture of azo polymers, the synthetic methods and their most important functions, such as photoinduced birefringence and dichroism, surface-relief-grating (SRG) formation, and light-driven deformation of liquid crystal elastomers. It combines a general survey of the subject and in-depth discussions of each topic, including numerous illustrations, figures, and photographs. Offering a balance between an introduction to the core concepts and a snapshot of hot and emerging topics, it is of interest to graduate students and researchers working in this and related fields. Xiaogong Wang is a Professor at the Department of Chemical Engineering, Tsinghua University, China.
Keywords: Chemistry.; Polymers.; Amorphous substances.; Complex fluids.; Optical materials.; Electronic materials.; elektronické knihy; electronic books